พลวัตแนวคิดและปฏิบัติการและการปรับตัวของคณะกรรมการประสานงานองค์กรพัฒนาเอกชน หลังปี 2549 - นิภาวรรณ แก้วแสนทิพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This thesis aims to understand the conceptual and operational evolution of the Non-Governmental Organizations Coordinating Committee (NGO-COD) and its subsequent adjustments following the 2006 and 2014 coups. The research employs a theoretical framework grounded in civil society and framing concepts to analyze three prominent movements that emerged after the 2006 coup: the movement opposing the 2007 Constitution draft, the advocacy for sustainable agriculture, and the pursuit of community land title rights. Furthermore, it investigates three movements that occurred after the 2019 coup, namely the movement against the 2017 Constitution draft, the opposition to forest reclamation policies, and the resistance against the Tepa Coal Power Plant.The study identifies five distinct periods that delineate the dynamics and practices of non-governmental organizations. Firstly, from 1980 to 1991, the prevailing concept of community culture played a pivotal role in rural development initiatives following a transformative phase known as the "Post - forest break." Secondly, during the period from Black May-1992 to 2000, the intensive exploitation of resources by both the state and the market led to a proliferation of NGOs. Within the NGO-COD, two distinct approaches were observed: one focusing on supporting villagers in challenging state power and asserting community rights, while the other sought to directly advocate for development alternatives within the state apparatus. The third period, spanning from the Thaksin government until the 2006 coup, saw the NGO-COD attempting to influence state policies through its network, but eventually, it was supplanted by the state s intervention. Concurrently, endeavors were made to challenge state power and instigate a movement to oust the Thaksin government. The fourth period, from the 2006 coup to the 2014 coup, was marked by the NGO-COD s active engagement in the Anti-Thakin Movement, resulting in network polarization. The NGO-COD adapted through two distinct pathways: fostering a movement for structural change and evolving into a professional NGO. Despite an internal conflict during the fifth period (from the 2014 coup to the 2019 elections), the pursuit of structural change, including counter-state policies, prominently characterized this phase. Some organizations embraced professionalization, while others opted to integrate with the state. Regarding the self-adjustment of the NGO-COD after the 2006 coup, the research reveals a narrower focus within the NGO landscape, primarily driven by internal conflicts. Four key adaptation efforts emerged during this period: 1) comprehensive analysis and restructuring through the constitutional framework, 2) transformation into professional organizations, 3) navigating conflict contexts to counter state policies, and 4) forging collaborations and integration with state institutions.